A nationwide survey on tracheostomy for very‐low‐birth‐weight infants in Japan. Issue 1 (7th December 2018) - Kurata, Hiroaki; Ochiai, Masayuki; Inoue, Hirosuke; Ichiyama, Masako; Yasuoka, Kazuaki; Fujiyoshi, Junko; Matsushita, Yuki; Honjo, Satoshi; Sakai, Yasunari; Ohga, Shouichi; ,
Abstract : Objectives: Tracheostomy is indicated for very‐low‐birth‐weight infants (VLBWIs) with prolonged respiratory problems during the perinatal period. The objective of this study is to clarify the epidemiology and risk factors in VLBWIs with tracheostomy after birth in Japan. Methods: A total of 40 806 VLBWIs were registered in the Neonatal Research Network of Japan database from 2003 to 2012. Among them, 34 674 infants (85%) survived over 28 days after birth and were subjected to this study. The clinical variables at birth, outcomes at hospital discharge and associated factors for tracheostomy were examined. Results: The proportion of VLBWIs with tracheostomy did not increase during the study period (mean 36 cases per year, 0.93%). The rate of in‐hospital death over 28 days after birth did not differ between tracheostomized and non‐tracheostomized infants (2/324, 0.6% vs 314/34 350, 0.9%). Tracheostomized infants more frequently had severe or moderate bronchopulmonary dysplasia (BPD) (75.5% vs 26.0%, P < 0.01) and longer hospitalization (229 days vs 83 days, P < 0.01) than non‐tracheostomized infants. Tracheostomized patients showed higher comorbidities with hypoxic ischemic encephalopathy (odds ratio [OR] 10.98, P < 0.01), muscular disease (OR 10.95, P < 0.01), severe or moderate BPD (OR 7.79, P < 0.01), chromosomal abnormality (OR 4.43, P < 0.01) or sepsis (OR 1.78, P < 0.05) at hospital discharge than non‐tracheostomized patients. Conclusion: We demonstrated the non‐increasing rate in tracheostomy for VLBWIs and such cases were associated with an excellent survival in Japan. These data provide evidence that more attentive care must be practiced in order to reduce the pulmonary and neuromuscular burdens of VLBWIs at birth.